2009
DOI: 10.1111/j.1526-100x.2008.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Native and Non‐Native Grassland Plant Communities on Breeding Passerine Birds: Implications for Restoration of Northwest Bunchgrass Prairie

Abstract: One common problem encountered when restoring grasslands is the prominence of non-native plant species. It is unclear what effect non-native plants have on habitat quality of grassland passerines, which are among the most imperiled groups of birds. In 2004 and 2005, we compared patterns of avian reproduction and the mechanisms that might influence those patterns across a gradient of 13 grasslands in the Zumwalt Prairie in northeastern Oregon that vary in the degree of non-native plant cover (0.9-53.4%). We mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…Most studies have indicated that the invasions by exotic plants negatively affect local breeding birds by decreasing species richness and/or abundance of birds (Benoit and Askins 1999;Fandino et al 2010;Flanders et al 2006;Skórka et al 2010), by causing the disappearance of some guilds (Ellis 1995;Hunter et al 1988;Mitra and Sheldon 1993), by reducing breeding success (Borgmann and Rodewald 2004;Mermoz and Reboreda 1998;Nordby et al 2009;Remeš 2003;Schmidt and Whelan 1999), by decreasing the growth rate of nestlings (Lloyd and Martin 2005), and by reducing nest-site fidelity (Ortega et al 2006). Other studies, however, have indicated that exotic plants could provide alternative or new breeding habitats for the local birds (Schmidt et al 2005;Sogge et al 2008;Whitt et al 1999) and that the breeding success in exotic habitats is equal to or even higher than that in native habitats (Kennedy et al 2009;Schlossberg and Kings 2010). Moreover, some birds in previously degraded ecosystems might depend on the exotic plants completing life histories (Fleishman et al 2003;Heckscher 2004;Safford 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Most studies have indicated that the invasions by exotic plants negatively affect local breeding birds by decreasing species richness and/or abundance of birds (Benoit and Askins 1999;Fandino et al 2010;Flanders et al 2006;Skórka et al 2010), by causing the disappearance of some guilds (Ellis 1995;Hunter et al 1988;Mitra and Sheldon 1993), by reducing breeding success (Borgmann and Rodewald 2004;Mermoz and Reboreda 1998;Nordby et al 2009;Remeš 2003;Schmidt and Whelan 1999), by decreasing the growth rate of nestlings (Lloyd and Martin 2005), and by reducing nest-site fidelity (Ortega et al 2006). Other studies, however, have indicated that exotic plants could provide alternative or new breeding habitats for the local birds (Schmidt et al 2005;Sogge et al 2008;Whitt et al 1999) and that the breeding success in exotic habitats is equal to or even higher than that in native habitats (Kennedy et al 2009;Schlossberg and Kings 2010). Moreover, some birds in previously degraded ecosystems might depend on the exotic plants completing life histories (Fleishman et al 2003;Heckscher 2004;Safford 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Characteristics of the edges included the height and variability of the vegetation within the edge; the management of the edge: whether it had been mown since the start of the growing season or affected by herbicide drift; the width and length of the edge; and the amount of bare ground [23] around the sample location. Variability was calculated as the standard deviation of the height measurements.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Located at an elevation of 1,100-1,700 m, the Preserve receives a mean annual precipitation of 43.3 cm/yr, and has an average maximum temperature of 26.98C in August and an average minimum temperature of À7.98C in December (30-year average, 1971-2000, at Joseph, OR, NOAA 2010. Although the Zumwalt Prairie has been used as summer pasture for horse, sheep, and cattle for over 100 years, the majority of the area remains dominated by native species including Idaho fescue (Festuca idahoensis), prairie Junegrass (Koeleria macrantha), and bluebunch wheatgrass (Pseudoroegneria spicata) (Kennedy et al 2009, Bartuszevige et al 2012. In addition, a rich forb community (.112 species of forbs) is associated with a diverse bee community (.200 species in 27 genera), with the most common genera being sweat bees of the genus Lasioglossum (Halictidae) and bumble bees (Bombus: Apidae) (Kimoto et al 2012).…”
Section: Study Areamentioning
confidence: 99%